Current Situation in Turkish Sericulture Sector - POLAT, M.; CEVGER, Y. (National Documentation Centre (EKT), 2018)
The purpose of this study is to assess sericulture sector according to actual data which has both cultural and economic value for Turkey and has feature of being a livestock sub-production area mostly considered as a source of additional income. Fresh cocoon, being the output of sericulture, is an important raw material for silk and silky textile industry and also has a traditional and cultural value. The situation assessment was made in terms of production level discussing the fresh cocoon data in Turkey by years. In Turkey, as of 2016, the annual cocoon production is 103 tons, and 2,001 families deal with this occupation. The organization and historical process of sericulture sector was discussed and the supports provided and changes over the years in sericulture sector were examined. The organization in sericulture dates back to old times. In 1940, the first cooperatives were founded in Bursa, Bilecik and Adapazarı in order to maintain and increase the cocoon production after the foundation of the Republic. These cooperatives were merged and Bursa Association of Agricultural Sales Cooperatives for Silk Cocoons (KOZABİRLİK) was founded on 11 May 1940. Although the support given to sericulture has changed over the years, is very important for the sector. By 2016, the purchase price of cocoons was 5 TL / kg while the price of support was 40 TL / kg. Some inferences were made about the market and foreign trade by taking into account the silky textile and silk carpet exportation, being the strength of the sector. Despite the decrease in export amount in recent years, only silk carpet exports have generated nearly 100 million dollars in income in the last 5 years. The key problems, faced in sericulture sector were determined and then to draw attention to these problems. The current situation assessment was made in the conclusion by making general inferences about the sector.
Keywords: 2. Zero hunger; 11. Sustainability